2014
DOI: 10.1007/s11606-014-3057-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HBV Preventive Services in a Medically Underserved Asian and Pacific Islander Population Using Provider and Patient Data

Abstract: BACKGROUND: Hepatitis B (HBV) represents a significant health disparity among medically underserved Asian and Hawaiian/Pacific Islander (API) populations. Studies evaluating adherence to HBV screening and vaccination guidelines in this population are limited. OBJECTIVE: The purpose of this study was to evaluate HBV screening and vaccination practices using both provider self-report and patient records. DESIGN: Medical records for 20,574 API adults were reviewed retrospectively and primary care providers were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Moreover, in a previously published study of providers and patients in the San Francisco safety net, we found that provider self-report of HBV screening and immunization practices generally aligned with objective measures of clinical practice derived from electronic medical record data, adding further value to these findings. 12 The generalizability of our findings may be limited by the possible heightened awareness of HBV among providers and patients in the San Francisco bay area as a result of community outreach efforts. However, the fact that HBV prevention and management practices remained suboptimal suggests that these efforts alone do not address the gaps in HBV care and reflects a potential for even higher gaps in HBV care in other regions of the country.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, in a previously published study of providers and patients in the San Francisco safety net, we found that provider self-report of HBV screening and immunization practices generally aligned with objective measures of clinical practice derived from electronic medical record data, adding further value to these findings. 12 The generalizability of our findings may be limited by the possible heightened awareness of HBV among providers and patients in the San Francisco bay area as a result of community outreach efforts. However, the fact that HBV prevention and management practices remained suboptimal suggests that these efforts alone do not address the gaps in HBV care and reflects a potential for even higher gaps in HBV care in other regions of the country.…”
Section: Discussionmentioning
confidence: 85%
“…11 Previously, our group has published on HBV screening practices among providers of a San Francisco safety-net health care system that serves uninsured and underinsured populations. 1214 We showed that among APIs, less than two thirds underwent HBV testing and less than 50% of susceptible patients were vaccinated for HBV. 12 Moreover, based on self-report, over 40% of providers were unfamiliar with HBV screening guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Background U.S. rates of the hepatitis A virus (HAV) and hepatitis B virus (HBV) have been steadily dropping since the introduction of the HAV and HBV vaccines in 1995 and 1982, respectively (Bondesson & Saperston, 1996); however, vaccination coverage in adults for vaccine-preventable diseases is still low for most routinely recommended vaccinations (Williams et al, 2015). Currently, adults who may be traveling to HAV or HBV endemic areas, those who have had or who are at risk for contracting sexually transmitted infections (STIs), inmates in correctional facilities, and members of medically underserved Asian groups are recommended to receive vaccination against hepatitis A and B (Keystone, 2009;Mukhtar et al, 2015). Furthermore, HBV has been identified as a public health problem for homeless individuals (Nyamathi et al, 2015), injection drug users (Kamath, Shah, & Hwang, 2014), and adults living in skilled nursing facilities (Annunziata, Rak, Del Buono, DiBonaventura, & Krishnarajah, 2012).…”
mentioning
confidence: 99%
“…1,2 The study by Mukhtar and colleagues highlights some of the barriers to hepatitis B screening. 3 Not surprisingly, testing rates for hepatitis B were positively associated with provider attitudes and negatively associated with providers' perceived barriers to testing. Notably, provider knowledge was not associated with testing.…”
mentioning
confidence: 95%